2018
DOI: 10.1108/maj-07-2017-1601
|View full text |Cite
|
Sign up to set email alerts
|

Lead engagement partner workload, partner-client tenure and audit reporting lag

Abstract: Purpose Motivated by a recent call from DeFond and Zhang (2014) for auditing scholars to use “a richer set of audit firm, auditor office, and individual auditor characteristics to capture competency”, this study aims to extend the related line of research by examining the association between lead engagement partner workload, defined as the number of public listed clients the partner is in charge of, and audit lag. The moderating effects of partner tenure on the partner workload–audit lag relationship have also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 61 publications
5
51
0
3
Order By: Relevance
“…Compared with the developed economies, the result shows that ARL in Oman is somewhat close to ARL in the US and UK, on average, 55 and 64 days respectively (Abernathy et al, 2014;Ghafran &Yasmin, 2018). And compared with the developing markets, such as Egypt and Malaysia, the average of ARL is 72 and 103 respectively (Khlif & Samaha, 2014;Wan-Hussin et al, 2018), indicating that ARL in Oman is shorter. It is believed that this variance in ARL is basically due to the difference in deadline of reporting among countries.…”
Section: Empirical Modelmentioning
confidence: 82%
See 1 more Smart Citation
“…Compared with the developed economies, the result shows that ARL in Oman is somewhat close to ARL in the US and UK, on average, 55 and 64 days respectively (Abernathy et al, 2014;Ghafran &Yasmin, 2018). And compared with the developing markets, such as Egypt and Malaysia, the average of ARL is 72 and 103 respectively (Khlif & Samaha, 2014;Wan-Hussin et al, 2018), indicating that ARL in Oman is shorter. It is believed that this variance in ARL is basically due to the difference in deadline of reporting among countries.…”
Section: Empirical Modelmentioning
confidence: 82%
“…Given the importance of audit lag to investors, identifying the determinants of audit lag has been of interest of scholars as exhibited in recent research conducted by Abernathy et al (2017), Sharma, Tanyi and Litt (2017), Wan-Hussin, Bamahros and Shukeri (2018) and Salehi, Bayaz and Naemi (2018). However, very few empirical studies investigated the factors impacting the lag of audit report in the MEC particularly with factors of corporate governance (see for example Afify, 2009;Baatwah et al, 2015a;Basuony et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also suggest that individual audit partners with more workload are likely to have a bearing on the audit quality (Gul et al, 2017;DeFond& Zhang, 2014). A recent study by Wan Hussin et al (2018) argues that auditors observed to prolong audit reports lag, due to the busy schedule. Partner level audit quality research is limited to data because it requires the audit report to be signed by the audit partner with their name disclose in the report.…”
Section: Background and Previous Literaturementioning
confidence: 99%
“…Hasil pengujian (Tabel 6) menunjukkan bahwa audit client tenure bukan merupakan variabel yang menentukan praktik opinion shopping atau membuktikan secara empiris bahwa ternyata audit client tenure tidak ber pengaruh positif. Hasil tersebut tidak men dukung sejumlah peneliti (Brown & Popo va, 2016;Elder, Lowensohn, & Reck, 2015;Gul, Ma, & Lai, 2017;Hussin, Bamahros, & Shukeri, 2018) yang justru menemukan ha sil sebaliknya. Meskipun demikian, peneli tian ini mendukung temuan Karim, Robin, & Suh (2016) karena mereka tidak memiliki bukti yang kuat untuk menyatakan bahwa auditor tenure dapat meningkatkan atau malah menurunkan kualitas proses audit.…”
Section: Metodeunclassified